The Islamic trend in children's literature according to Abi al-Hasan Ali al-Nadwi R. h - Muhammad Abdul Rehman; Abbas Ali Raza (jihat-ul-islam, 2022)
Mr. Abi Al-Hassan Al-Nadawi, who wrote a lot about children’s literature, who cared about children a lot because they are the mother’s wealth and future, and he is a great legacy for the Islamic mother. He has more than two hundred authors in the Arabic language and dozens in the Persian and Urdu languages, and abundant knowledge that scholars spoke about and books and compilations were written for him. This is what The Indian scholar, Sheikh Abu Al-Hassan Al-Nadawi, left him, whose fame reached the horizons and reached a rank that few of his peers achieved in his era and time, so his condition was unique and what he gave to his nation and society was great. With the increase of Al-Nadawi's fame as an Islamic thinker, there is an important aspect of this rich personality, which is the literary aspect, especially Arabic and Islamic literature.Here we are talking about the goals of Allama Al-Nadawi in what he wrote for the Muslim child. These goals contain a number of topics, namely: the Muslim language, advocacy, Islamic education, the intellectual and psychological aspect, Islamic culture, adherence to religion, religious deeds, and legal beliefs, which highlight several aspects of thought, language, and education. And children’s literature through the researcher’s careful study of the books of Allamah al-Nadawi in it. Here we discuss these objectives in some detail in light of his writings and books.